Molecular Characterization Analysis of Prevalent Infectious Bronchitis Virus and Pathogenicity Assessment of Recombination Strain in China - Wu, Zhiqiang; Fang, Huanxin; Xu, Zhouyi; Lian, Jiamin; Xie, Zi; Wang, Zhanxin; Qin, Jianpin; Huang, Benli; Feng, Keyu; Zhang, Xinheng; Lin, Wencheng; Li, Hongxin; et al. (Frontiers in Veterinary Science, 2022)
Avian coronavirus infectious bronchitis virus (IBV) is a respiratory pathogen of chickens, resulting in severe economic losses in the poultry industry. This study aimed to monitor and isolate the molecular identity of IBV in broiler flocks with respiratory symptoms in eight provinces of China. In total, 910 samples (oropharyngeal and cloacal mixed swabs) from broiler flocks showed IBV positive rates of 17.6% (160/910) using PCR assay. Phylogenetic analysis of the complete S1 genes of 160 IBV isolates was performed and revealed that QX-type (GI-19), TW-type (GI-7), 4/91-type (GI-13), HN08-type (GI-22),TC07-2-type (GVI-1), and LDT3-type (GI-28) exhibited IBV positive rates of 58.15, 25, 8.12, 1.86, 5.62, and 1.25%. In addition, recombination analyses revealed that the four newly IBV isolates presented different recombination patterns. The CK/CH/JS/YC10-3 isolate likely originated from recombination events between strain YX10 (QX-type) and strain TW2575-98 (TW-type), the pathogenicity of which was assessed, comparing it with strain GZ14 (TW-type) and strain CK/CH/GD/JR07-7 (QX-type). The complete S1 gene data from these isolates indicate that IBV has consistently evolved through genetic recombination or mutation, more likely changing the viral pathogenicity and leading to larger outbreaks in chick populations, in China.